Identification of Core DNA Elements that Target Somatic Hypermutation - Kohler, Kristin M. (2012)
Somatic hypermutation (SHM) diversifies the variable region of Ig genes and underlies the process of affinity maturation, in which B lymphocytes producing high affinity antibodies are generated and selected. SHM is triggered in activated B cells by deamination of deoxycytosine residues mediated by activation-induced deaminase (AID). While mistargeting of SHM and AID results in mutations and DNA damage in many non-Ig genes, they act preferentially at Ig loci. The mechanisms responsible for preferential targeting of SHM and AID activity to Ig loci are poorly understood. Using an assay involving a SHM reporter cassette inserted into the Ig light chain locus (IgL) of chicken DT40 B cells, we have identified a 1.9 kb DIVAC (diversificationactivator) element derived from chicken IgL that supports high levels of AID-dependent mutation activity. Systematic deletion analysis reveals that targeting activity is spread throughout much of the sequence and identifies two core regions that are particularly critical for function: a 200 bp region within the IgL enhancer, and a 350 bp 3′ element. Chromatin immunoprecipitation experiments demonstrate that while DIVAC does not alter levels of several epigenetic marks in the mutation cassette, it does increase levels of serine-5 phosphorylated RNA polymerase II in the mutation target region, consistent with an effect on transcriptional elongation/pausing. We propose that multiple, dispersed DNA elements collaborate to recruit and activate the mutational machinery at Ig gene variable regions during SHM.